SOLAR SYSTEM OSCILLATIONS AND MODELS OF NATURAL PROCESSES - Berry B.L. (My University, 2006)
Tidal and momentum interactions of the bodies of the solar system create stable oscillations of the momenta of inertia of the Sun and planets. The laws of momentum conservation are the reasons for synchronous oscillations, which are observed in geodynamic, solar and climatic processes. The stable harmonics of the processes have to be detected from representative sets of helio-geophysical data. The regular parts of natural processes can be modelled by the sum of the stable harmonics. © 2005 Elsevier Ltd. All rights reserved.
Keywords: HARMONIC MODELS; SOLAR ACTIVITY; STABLE OSCILLATIONS; TERRESTRIAL PROCESSES; SOLAR SYSTEM